Postawa Ukraińców wobec agresji III Rzeszy na Polskę i okupacji we wspomnieniach polskich lekarzy = Attitude of Ukrainians towards the aggression of the Third Reich against Poland and the occupation in the memories of Polish physicians - Kopocińśki, Zbigniew; Kopociński, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the interwar period, Ukrainians were a national minority inhabiting the south-eastern provinces of Poland. The Ukrainian chauvinists from the Organization of Ukrainian Nationalists who hated Poland were of great influence there.
Keywords: Eastern Borderlands; Lvov; genocide; Volyn; Ukrainian nationalism; Kresy Wschodnie; ludobójstwo; Lwów; Wołyń; nacjonalizm ukraiński